Response of lettuce cultivars to Meloidogyne javanica and Meloidogyne incognita race 1 and 2 - Correia, Érika Cristina; da Silva, Norberto; Costa, Marylia Gabriella; Wilcken, Silvia Renata (Revista Ciência Agronômica, 2018)
The aim of this study was to evaluate resistance to Meloidogyne javanica and Meloidogyne incognita race 1 and 2 in the American group of lettuce cultivars. Two days after transplanting, the plants were inoculated with 5,000 eggs and potential second-stage juveniles of the nematode under test per pot. The Rutgers tomato was used as the standard for the viability of Meloidogyne javanica and Meloidogyne incognita race 1 and 2. The variables to be evaluated were gall index, egg mass index and nematode reproduction factor, which were evaluated 60 days after inoculation. The results showed that the Ithaca, RS-1397, Raider Plus, Challenge, L-104, IP-11, Salinas 88, Calona, Desert Queen, Classic and Vanguard 75 cultivars were resistant to Meloidogyne incognita race 1, with a reproduction factor which ranged from 0.19 to 0.88, and that the Desert Queen, L-104, Salinas 88, Vanguard 75, Robinson, RS-1397, Challenge, Raider Plus, Classic, Calona, Ithaca, Lady, IP-11 and Winterset cultivars were resistant to Meloidogyne incognita race 2, with a reproduction factor of between 0.23 and 0.93. All the cultivars under evaluation were resistant to Meloidogyne javanica, with a reproduction factor of less than 1.0.